Cryptography for Information - Xayxanadasy, Kedtysack; Khaminsou, Bounmy; Thanavanh , Pinkham; Phosipong, Phailin (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The aim of this study is to apply mathematics methods into the encryption and decryption for communication such as text message, email and so on. Furthermore, this includes how to write scripts with algorithm by Python programming of each method of the encryption and decryption. The result indicates that the encryption and decryption are essential for electronic communication especially business areas for protecting the data and information from hacking or hackers. In this article, We will study Three types of encryption and decryption such as Caesar cipher, Affine cipher and RSA cipher are examined in this study.